Evaluation of The Fulfillment of The Defendant's Rights in Online Criminal Proceedings in Indonesia - Gede Aditya Pratama (Jurnal Hukum Sasana, 2023)
In early 2020, Indonesia was hit by the Corona Virus that affect all aspects in public live including affect judicial institutions. Criminal proceedings that supposed to be held in a trial that open to the public according to the Indonesian Criminal Procedure Code, must be held online in which judges, prosecutor, lawyer, and the defendant are in separate places. Even though, the Indonesian Supreme Court have enacted Circular Letter No. 1 Year 2020 to regulate the proceedings during the Covid-19 pandemic, many criticisms for the course of online trials especially regarding the rights of the defendants, which were violated during the online trial. The rights of the defendant who were violated during the online criminal trial were the right to be heard equally, right to consult with a lawyer during the proceedings of the case, right to be tried without undue delay, and right to present witnesses and experts and ask questions to these witnesses and experts. These rights, that was feared violated because the defendant could not attend the trial in person. This research was conducted to explain the course of the online criminal proceeding to assess whether the defendant’s rights had been fulfilled during the online trial.